Acute and chronic toxicity of nitrate to fat greenling (Hexagrammos otakii) juveniles. Issue 5 (13th March 2019) - Yang, Xiaohan; Peng, Lei; Hu, Fawen; Guo, Wen; Hallerman, Eric; Huang, Zhitao
Abstract : We evaluated the acute and chronic toxicity of nitrate to juvenile fat greenling Hexagrammos otakii . The 24‐, 48‐, 72‐, and 96‐hr LC50 s of nitrate to 1.91 ± 0.7 g greenlings were 2, 741, 2, 413.5, 2, 357.6, or 2, 339.2 mg/L nitrate‐N, respectively. Greenlings (6.55 ± 1.83 g) were exposed to 5 mg/L (control) and 157 mg/L for 4 weeks in a recirculating aquaculture system. After 4 weeks, length, weight, feed conversion ratio, and specific growth rate were significantly ( p < 0.05) lower for nitrate‐exposed fish than for control fish. Elevated nitrate exposure was associated with decreased plasma hemoglobin concentration and red blood cell count. Our results demonstrate that nitrate poses a threat to greenlings and provide information that is useful for establishing water quality criteria for early life stages of this cultured fish. The sensitivity of greenlings to elevated NO3 − should be evaluated at other life stages to determine how chronic exposure might impact survival, growth, health, reproductive success, and harvest quality.